Global Leadership Initiative on Malnutrition and Mini Nutritional Assessment in Evaluation of Nutritional Status of COVID-19 Patients - Navid Sherafati; Mehrdad Behzadi; Mohammad Vesal Bideshki; Matin Najafian; Mohammad Reza Jowshan; Zahra Hosseinzade; Bahman Panahande; Zaker Saeedinejad; Narges Roustaei; Janmohammad Malekzade; Azizollah Pourmahmoudi (International Journal of Nutrition Sciences, 2024)
Background: Considering that nutritional status is one of the influential factors in the process of recovery of patients with COVID-19, this study was conducted to determine the nutritional status of COVID-19 patients and its relationship with clinical outcomes.Methods: This cross-sectional study included 155 patients diagnosed with COVID-19 disease (18-80 years) using PCR test and chest CT scan. The nutritional status of participants was assessed employing Mini Nutritional Assessment (MNA) questionnaire, Global Leadership Initiative on Malnutrition (GLIM) criteria, and Nutrition Risk in Critically(NUTRIC) score.Results: Among 81 men (52.3%) and 74 women (47.7%) based on MNA, 30 participants (19.4%) and based on GLIM criteria, 42 participants (27.1%) suffered from malnutrition. Also, systolic and diastolic blood pressure (GLIM: p=0.038, p=0.008, respectively; MNA: p=0.04, p=0.01, respectively) and blood oxygen saturation (MNA: p=0.01; GLIM: p=0.012)were significantly associated with nutritional status of participants. MNA and GLIM findings showed a relative agreement of 0.35 (p<0.0001).Conclusion: Nutritional status was demonstrated to be a critical factor that can affect the clinical condition and recovery process of COVID-19 patients. GLIM was shown to be practical and reliable criteria to measure the nutritional status for diagnosis and prognosis of patients with COVID-19.